Nickel hydroxide armour promoted CoP nanowires for alkaline hydrogen evolution at large current density. (5th January 2022) - Wang, Fu-Li; Zhou, Ya-Nan; Lv, Jing-Yi; Dong, Bin; Zhang, Xin-Yu; Yu, Wen-Li; Chi, Jing-Qi; Wu, Ze-Xing; Wang, Lei; Chai, Yong-Ming
Abstract: The development of hydrogen evolution activity (HER) electrocatalyst that can run durably and efficiently under the large current density is of special significance but still challengeable for the massive production of hydrogen. Herein, a CoP/Ni(OH)2 nanowire catalysts grown on Co foam (CF) with a three-dimensional heterojunction structure has been successfully prepared by electrodepositing nickel hydroxide on the surface of cobalt phosphide. The prepared CoP/Ni(OH)2 –15 min sample reveals a superior HER activity and stability. It merely requires ultralow overpotentials of 108 and 175 mV to 100 and 500 mA cm −2, respectively. In addition, the long-term stability test shows that the catalyst (CoP/Ni(OH)2 –15 min) can operate stably for at least 70 h at 400 mA cm −2 . Utilizing NiFe-LDH/IF with high OER activity, the NiFe-LDH/IF || CoP/Ni(OH)2 –15 min catalyst system possesses the same outstanding performance for overall water splitting (OWS), which can accomplish ≈ 500 mA cm −2 at 1.74 V in 1 M KOH electrolyte. Moreover, the NiFe-LDH/IF || CoP/Ni(OH)2 –15 min couple can work for more than 80 h at 500 mA cm −2, indicating its a great prospect in the area of electrolysis water. Such excellent catalytic performance is mainly attributed to the armor effect of Ni(OH)2, which can not only promote the rapid decomposition of water molecules, but also prevent the loss of phosphorus and enhance the synergistic effect of CoP and Ni(OH)2 . This work can offer a significant reference for the design with high-performance and durable transition metal phosphide electrocatalysts. Graphical abstract: Image 1 Highlights: CoP/Ni(OH)2 nanowire is prepared by molten salt method and electrodeposition. Ni(OH)2 can improve water dissociation activity and prevent the loss of P from CoP. CoP/Ni(OH)2 –15 min requires 108 and 175 mV at 100 and 500 mA cm −2, respectively. (CoP/Ni(OH)2 –15 min) operates stably for at least 70 h at 400 mA cm −2 for HER. CoP/Ni(OH)2 –15 min possesses more than 80 h at 500 mA cm −2 for water electrolysis.